Urban Waste Sinks as a Natural Resource: The Case of the Fraser River - Keeling, Arn (Urban History Review / Revue d'histoire urbaine, 2005)
The discursive and material construction of rivers as natural waste-treatment systems highlights important historical connections between urban sanitary networks, conservation ideology, and urban environmental values in the twentieth century. Early-mid-century sanitary engineers oversaw the transformation of space and nature in North American cities through the planning and construction of sewerage and drainage networks. In doing so, they drew from the ideas and methods of the technocratic conservation movement, which advocated the expert management of natural resources to ensure their maximum beneficial utilization. Pollution control and conservation were linked through the doctrine of “assimilative capacity,” a concept used by engineers to describe the ability of natural waters to absorb, dilute, and disperse urban and industrial wastes. Using powerful new quantitative representations of nature, sanitary engineers proposed to incorporate natural biophysical processes into technological networks for waste disposal. This approach to urban waste-disposal problems is exemplified by the case of Vancouver's Fraser River, which was enrolled by engineers and planners as a sink for urban wastes. However, the attempt to construct the river as a kind of “organic machine” for waste disposal resulted in long-term environmental problems in the river's estuary. By the late 1960s, this pollution, along with Vancouverites' changing environmental values, led to political and social protest over the exploitation and degradation of the river.